The Impact of Congenital Heart Disease to Brain Development and Neurodevelopmental Outcome : A Ten Years Systematic Review - Sriwaningsi, Lina; Oktadiputra, Ery (International Medical Journal Corp. Ltd, 2024)
Background: CHD affects millions of newborns worldwide, causing neurodevelopmental abnormalities. Early interventions, such as medications, can protect the brain and prevent complications. However, little is known about the effects of CHD on neurodevelopmental outcomes in newborns following open-heart surgery. Methods: This systematic review, which followed PRISMA 2020 guidelines, concentrated on full-text English literature that was released between 2014 and 2024. The literature was gathered utilizing a variety of online resources, such as ScienceDirect, PubMed, and SagePub. Result: After a detailed screening process including three levels, five papers were found to have relevant links to our current comprehensive study. After that, these pieces were given additional attention, and the entire text was carefully examined. Conclusion: Early intervention in infants with CHD significantly improves outcomes, focusing on neurodevelopment and quality of life, despite challenges in determining motor outcomes.